Vacation Over : Implications for the Caribbean of Opening U.S.-Cuba Tourism - Romeu, Rafael (IMF Working Papers; Working Paper, 2008)
An opening of Cuba to U.S. tourism would represent a seismic shift in the Caribbean's tourism industry. This study models the impact of such a potential opening by estimating a counterfactual that captures the current bilateral restriction on tourism between the two countries. After controlling for natural disasters, trade agreements, and other factors, the results show that a hypothetical liberalization of Cuba-U.S. tourism would increase long-term regional arrivals. Neighboring destinations would lose the implicit protection the current restriction affords them, and Cuba would gain market share, but this would be partially offset in the short-run by the redistribution of non-U.S. tourists currently in Cuba. The results also suggest that Caribbean countries have in general not lowered their dependency on U.S. tourists, leaving them vulnerable to this potential change.